(untitled) (Nepal Agriculture Research Journal, 2009)
If the EST primers designed for one species can be used in related species, then the cost involved in developing markers for DNA fingerprinting, genetic relationship studies, mapping, etc. for other species is significantly reduced. We tested the applicability of 17 EST primers developed from common buckwheat in other wild and cultivated Fagopyrum species. A total of 18 accessions consisting of 4 subspecies and 2 species were used. Sequences of 93 cDNA clones were used to design primers using Primer3. Amplification products were different in band intensity. In most of the cases, the bands of F. homotropicum were with high intensity. All primers showed single band except in Accession C9022. Three primers 23, 31 and 69 produced very clear singe band. All primers amplified the genomic DNA of F. homotropicum (2x). Eight primers amplified the DNA of all accessions. Results indicated that the transferability of EST markers developed for common buckwheat decreased with an increase in genetic distance between them. Key words: Common buckwheat; EST markers; Fagopyrum species; transferability DOI: 10.3126/narj.v7i0.1863 Nepal Agriculture Research Journal Vol.7 2006 pp.27-36